An Innovation Ecosystem Game Study: The Role of Noncontractual Mechanisms - Ying Gao; Zihan Zhu; Fulei Shi (Journal of Mathematics)
Innovation ecosystem management is now a new paradigm in innovation management research. Innovation ecosystems are dynamic innovation alliances based on noncontractual governance. In this paper, a traditional cooperative innovation game model and a cooperative innovation game model with noncontractual mechanism are developed and compared. The results show that the cooperation formed only by contractual mechanisms’ model is unstable and the system is likely to collapse. The noncontractual mechanism can be used as a supplement to the contractual mechanism to make the game develop towards a stable “cooperation-cooperation” state. The research conclusion of this paper will make the core companies in the innovation ecosystem realize the important role of noncontractual mechanism and help them make decisions.